Prevalence of HSV‐1/HSV‐2 and CMV Infections in Infertile Men and Their Impact on Sperm Parameters: A Cross‐Sectional Study in Iran - Seyed Mansour Salar; Fahime Edalat; Arash Letafati; Seyed Mehdi Kalantar; Fatemeh Javanmardi; Ahmad najafi; Mahmoud vakili; Afagh Moattari (Health Science Reports)
ABSTRACT Background and Aims Viral infections are significant contributors to infertility. This study aimed to determine the prevalence of Herpes Simplex Virus 1 and 2 (HSV‐1/HSV‐2) and cytomegalovirus (CMV) infections in men with infertility, compared to a control group of fertile men. Methods A cross‐sectional study was conducted with seminal fluid samples from 100 fertile and 100 infertile men, aged 20–40 years, referred to Yazd Infertility Center. DNA extraction was done using the AmpliSens kit, and the presence of CMV and HSV‐1/HSV‐2 was determined via real‐time PCR. Sperm parameters (count, quick & slow, motility, morphology, and volume) were also assessed and compared to the control group. Results CMV infection was found in 16% of fertile and 10% of infertile men. HSV‐1/HSV‐2 prevalence was significantly higher in infertile men (32%) compared to fertile men (8%). Abnormal sperm count was significantly associated with HSV status (p = 0.001), as was abnormal morphology (p = 0.021), while abnormal quick & slow, motility and volume showed no significant association. Data analysis indicated no correlation between sperm parameters—including sperm quick & slow, motility, count, morphology, and semen volume—and CMV infection. Conclusion HSV infection is linked to sperm‐specific parameters, particularly count and morphology. These findings enhance our understanding of viral‐induced male infertility and underscore the need for targeted approaches to manage HSV‐1/HSV‐2‐related infertility.